The Urgency of Implementing Corruption Crime Asset Confiscation in The Context of Recovering State Losses - Anwar, Muhammad; Achmad Darodjat, Tubagus (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
Return of assets resulting from criminal acts of corruption based on Article 10 of the Criminal Code and Articles 18, 19 of Law no. 20 of 2001 concerning the Eradication of Corruption Crimes, cannot yet be used as a basis for maximizing the return of State losses, applying replacement money sanctions under Article 10 of KUHP and Articles 18 and 19 of UU TIPIKOR is fraught with difficulties. In court rulings for criminal acts of corruption that have permanent legal effects, the quantity of money resulting from the act and the burden of state losses in corruption are never equal (Inkracht). The amount returned to the state is reduced due to corruption crimes. In a judge's decision that has permanent legal force (Inkracht) ordering perpetrators of criminal acts of corruption to return the money that was corrupted and/or money obtained from criminal acts of corruption, in practice, it often happens that perpetrators are unable to pay replacement money, so they prefer to replace it with prison punishment. Prison sentences are often used as a loophole to avoid paying compensation so that the state still suffers losses even though it has been proven in court. Therefore, the appropriate strategy for recovering and returning state losses in the context of realizing state financial justice is to confiscate the assets of perpetrators of criminal acts of corruption by the value of the state losses incurred by corruption by giving the authority to the Public Prosecutor to submit asset confiscation to the court to confiscate the assets of perpetrators of criminal acts of corruption before a court decision or before there is a lawsuit.